2008
DOI: 10.1038/clpt.2008.168
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response of Ritonavir on Hepatic CYP3A Activity and Elvitegravir Oral Exposure

Abstract: Ritonavir, a potent inhibitor of cytochrome P450 isoform 3A (CYP3A) activity, is frequently used to boost the effects of protease inhibitors at doses of 100-400 mg per day; however, human data regarding the optimal dose required for boosting are limited. This study systematically evaluated the ritonavir dose-response relationship on presystemic and systemic CYP3A metabolism using the human immunodeficiency virus integrase inhibitor elvitegravir and midazolam as probe substrates. Ritonavir administered once dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 11 publications
7
87
0
Order By: Relevance
“…treatment (24); the pharmacokinetic variability could be also due to interpatient variability in CYP3A expression levels. Mathias et al showed a doseresponse relationship of ritonavir for inhibition of CYP3A activity and elvitegravir oral exposure in humans (25). Maximum inhibition of elvitegravir apparent oral clearance was achieved with ritonavir doses of 50 to 100 mg.…”
Section: Discussionmentioning
confidence: 99%
“…treatment (24); the pharmacokinetic variability could be also due to interpatient variability in CYP3A expression levels. Mathias et al showed a doseresponse relationship of ritonavir for inhibition of CYP3A activity and elvitegravir oral exposure in humans (25). Maximum inhibition of elvitegravir apparent oral clearance was achieved with ritonavir doses of 50 to 100 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ritonavir-mediated "boosting" of protease inhibitor-containing regimens has become a standard of care for nonpregnant adults. 47) Kosel and coworkers found that the induction of CYP3A4 during pregnancy was offset by this regimen, implying the usefulness of this prescription for pregnant women. 48) …”
Section: Fluctuation Of Cyp3a Activity During Pregnancymentioning
confidence: 99%
“…30 In contrast, the investigational integrase inhibitor elvitegravir, which is in late-stage development, is a CYP3A4 substrate and requires boosting with an inhibitor to achieve therapeutic concentrations. 31 Pharmacodynamic interactions may affect the efficacy or toxicity of a drug in an additive, synergistic, or antagonistic manner. An example of an undesirable HIV-related pharmacodynamic drug-drug interaction occurs with the combination of didanosine and tenofovir.…”
Section: Management Of Drug Interactionsmentioning
confidence: 99%